The leisure-time activities of foreign students in the University of the Philippines, Diliman (school year 1972-1973) - Tharasrisuthi, Nongyaw 1948- (s.n.], 1973)
This is a survey of the leisure-time activities of foreign students in the University of the Philippines, Diliman, Quezon City and its relation to sex, age and civil status.